Brain Shape Provides a Structural Mechanism for Postorbital Septation in Primates - DeLeon, Valerie B; Franklin, Katheryn P; Cunningham, Andreana S; Summers, Siobhan A; Bryson, Emily R; Vinyard, Christopher J; Smith, Timothy D (The FASEB journal, 2022)
Postorbital septation is a character that unites haplorhine primates. As a result, evidence of postorbital septation is expected for fossil primates that may be ancestral to both modern tarsiers and modern anthropoids. Our previous work on newborn primates has indicated that postorbital septation in tarsiers is secondary to growth of their large eyes. If this is the case, postorbital septation is convergent in tarsiers and anthropoids, and therefore should not be expected in their fossil ancestors. Here, we used morphometric analysis of the cranium and endocast of newborn and adult primates to show that postorbital septation in the order Primates may be explained by shape of the brain. We used a sample of over thirty species of modern primates representing all major clades, with individuals representing both newborn and adult stages. The newborn stage is most informative for understanding spatial relationships of soft tissues during formation of the skull. MicroCT image data were used to create virtual reconstructions of the cranium and endocast as an estimate of brain shape. Fixed landmarks were used to capture the shape of the cranium, and sliding semilandmarks represented the contour of frontal and temporal lobes on the endocast. As expected, morphometric analysis showed a significant effect of phylogeny on cranial and endocast shape in both newborns and adults. Notably, the phylogenetic effect was apparent in only the contours of the frontal and temporal lobes, independent of cranial shape. We present 3D models of the endocast and cranium of newborn primates to illustrate the spatial relationship of brain and facial structures as a mechanism for postorbital septation in anthropoid primates.